Strategic business models in the car provisioning undustry - optimizing the car sharing business model: short- and mid-term recommendations for the car sharing business model - Lohmann, Marc Adrian (2022)
Car sharing has been the subject of discussion in the context of future mobility. However, many car sharing providers struggle to achieve profitability. This study aims to analyze car sharing and business models in the car provisioning industry to develop concrete recommendations for optimizing the car sharing business model. After conducting a thorough review of all aspects of the car sharing business model, seven recommendations were identified and evaluated. We suggest that implementing dynamic pricing, utilizing vehicles for complementary cases, adding rental/subscription offerings, and preparing for the integration of autonomous vehicles will optimize the business model and ensure future competitiveness